Adult sex ratio and male body condition affect alternative reproductive tactics in a spider. (3rd December 2021) - Heimerl, Daniel; Dudová, Pavla; Wacker, Karoline; Schenkel, Elisa; Despréaux, Garance; Tuni, Cristina
Abstract: Biases in adult sex ratios can alter the intensity of sexual selection by enhancing competition for mates. Under intense competition males increase their investment in behaviors to outcompete rivals (e.g., fighting). Yet, given that in male-biased environments mating opportunities are rare males may alternatively reduce costly courtship and/or adopt alternative reproductive tactics (ARTs). Males of the spider Pisaura mirabilis adopt different mating tactics, offering females genuine nuptial gifts (prey), nutritionally worthless gifts (prey leftovers), or no gifts. To test whether behavioral shifts between gift tactics are triggered by changes in the competitive environment, we established replicate spider populations under natural conditions at varying adult sex ratios (male-biased, female-biased and equal) and sampled gift tactics repeatedly over time. We additionally explored how male individual traits, such as body size and condition, affect the expression of ARTs. In male-biased populations males produced more gifts but of low quality, suggesting competition to trigger increased mating effort to ensure mate acquisition and fertilizations, but through a worthless gift tactic. Production of gifts and of genuine gifts was favored by high body condition, pointing to energetic limitations as being central for male reproductive capacity. We hence highlight two co-existing mechanisms at play to explain ARTs in this system, the competitive social environment where expression of gift tactics is based on optimal-decision making to overcome competition, and a conditional strategy linked to the individual's energetic state. Abstract : When competitors are abundant but females are scarce male spiders modify their mating tactics: they produce more food gifts for the females, but of lower quality. This allows them to secure matings, while saving on the energetic costs of gift production.